Dysregulation of SOCS-Mediated Negative Feedback of Cytokine Signaling in Carcinogenesis and Its Significance in Cancer Treatment - Jiang, Mengmeng; Zhang, Wen-wen; Liu, Pengpeng; Yu, Wenwen; Liu, Ting; Yu, Jinpu (Frontiers in Immunology, 2017)
Suppressor of cytokine signaling (SOCS) proteins are major negative feedback regulators of cytokine signaling mediated by the Janus kinase(JAK)-signal transducer and activator of transcription signaling pathway. In particular, SOCS1 and SOCS3 are strong inhibitors of JAKs and can play pivotal roles in the development and progression of cancers. The abnormal expression of SOCS1 and SOCS3 in cancer cells is associated with the dysregulation of cell growth, migration, and death induced by multiple cytokines and hormones in human carcinomas. In addition, the mechanisms involved in SOCS1- and SOCS3-regulated abnormal development and activation of immune cells in carcinogenesis, including T cells, macrophages, dendritic cells, and myeloid-derived suppressor cells, are still unclear. Therefore, this study aims to further discuss the molecules and signal pathways regulating the expression and function of SOCS1 and SOCS3 in various types of cancer and elucidate the feasibility and efficiency of SOCS-based target therapeutic strategy in anticancer treatment.